Effect of Trichoderma viride on rhizosphere microbial communities and biocontrol of soybean root rot - Gao, Peixin; Qi, Kai; Han, Yujuan; Ma, Liguo; Zhang, Bo; Zhang, Yueli; Guan, Xiumin; Qi, Junshan (Frontiers in Microbiology, 2023)
Biological seed dressing is a cost-effective means to protect plant roots from pathogens. Trichoderma is generally considered as one of the most common biological seed dressings. However, there is still a dearth of information on the effects of Trichoderma on microbial community of rhizosphere soil. High-throughput sequencing was used to analyze the effects of Trichoderma viride and a chemical fungicide on microbial community of soybean rhizosphere soil. The results showed that both T. viride and chemical fungicide could significantly reduce the disease index of soybean (15.11 % for Trichoderma and 17.33 % for Chemical), while no significant difference was observed between them. Both T. viride and chemical fungicide could affect the structure of rhizosphere microbial community, they increased the β-diversity of microbial community and significantly reduce the relative abundance of Saprotroph-Symbiotroph. Chemical fungicide could reduce the complexity and stability of co-occurrence network. However, T. viride is beneficial for maintaining network stability and increasing network complexity. There were 31 bacterial genera and 21 fungal genera significantly correlated with the disease index. Furthermore, several potential plant pathogenic microorganisms were also positively correlated with disease index, such as Fusarium, Aspergillus, Conocybe, Naganishia and Monocillium. From this work, T. viride may be used as a substitute for chemical fungicide to control soybean root rot and be more friendly to soil microecology.